PENENTUAN STABILITAS SEDIAAN KRIM TABIR SURYA DARI BAHAN EKSTRAK RIMPANG KENCUR (Kaempferia galanga L.) - Widji Soeratri; Noor Ifansyah; Diana Fitrianingrum (The East Java Biological Society, 2005)
The objective of this research was to know the chemical stability of the etil para-metoksi sinamat (EPMS) formulated in sunscreen cream of oil in water base. The EPMS was isolated from Kaempferia galanga L. tuber pulvis with maceration-percolation method using ethanol 96%. The chemical stability of the EPMS formulated in sunscreen cream of the oil in water base was investigated by keeping the cream at room temperature. At appropriate interval the concentration of EPMS in cream was measured. The results showed that the EPMS formulated in sunscreen cream of oil in water base was unstable at room temperature for 70 days. The concentration of EPMS in cream significantly decreased after 70 days (p = 0,01) during keeping at room temperature with the coefficient degradation value (k)= 4.4.10-3/day.